Differential effects of palmitoleic acid on human lymphocyte proliferation and function. Issue 1 (December 2016) - Passos, M.; Alves, H.; Momesso, C.; Faria, F.; Murata, G.; Cury-Boaventura, M.; Hatanaka, E.; Massao-Hirabara, S.; Gorjão, R.
Abstract Background Palmitoleic acid (PA) is a n-7 monounsaturated fatty acid (MUFA) secreted by adipose tissue and related to decreased insulin resistance in peripheral tissues. Evidences have been shown that PA also decreased proinflammatory cytokine expression in cultured macrophages. Although studies have shown that other fatty acids (FAs) modulate several lymphocyte functions, the specific effect of PA on these cells is unknown. The aim of the present study was to evaluate the possible influence of PA on activation and differentiation of human lymphocytes in comparison to oleic acid (OA). Methods Human lymphocytes were isolated from peripheral blood of health men and cultured in the presence of growing concentrations of PA or OA (5 to 200 μM), for 24 h. After that, cells were collected and cytotoxicity evaluated by flow cytometry. Then, we analyzed proliferative capacity in lymphocytes treated with non toxic concentrations of PA and OA (25 and 50 μM, respectively), in the presence or absence of concanavalin A (ConA). The Th1/Th2/Th17 cytokine production was determined by theCytometric Bead Array . CD28 and CD95 surface expression and T regulatory cell percentage were determined by flow cytometry. Results We observed that PA is toxic to lymphocytes above 50 μM. PA promoted a decrease of lymphocyte proliferation stimulated by ConA in both concentrations. PA also decreased CD28 externalization and increased CD95. On the other hand, OA did not alter these parameters. In the same way, PA reduced IL6, IFN-gamma, TNF-alpha and IL17A production in both concentration and IL2 only at 50 μM (in the presence of ConA). OA promoted IFN-gamma reduction in both concentrations and an increase of IL-2, IL4 and IL10 at 25 μM. Both fatty acids decreased the percentage of T regulatory cells. Conclusion In conclusion, PA promoted a suppressive effect on lymphocyte proliferation characterized by a decrease of Th1 and Th17 response, and co-stimulatory molecule (CD28). However, OA increased lymphocyte proliferation through IL2 production and Th2 response. These results also show a more suppressive effect of PA on lymphocytes in comparison to OA.